La estructura interna del léxico disponible en español como lengua extranjera (ELE) de los preuniversitarios polacos - Antonio María López González (Studia Romanica Posnaniensia, 2014)
The technique for collecting available lexicon is based on surveys of open lists in which for two minutes informants recorded all the words that come to mind in relation to each center of interest, up to a total of 16 thematic stimuli. These stimuli were defined by Gougenheim et al. (1964) as the most universally representative semantic sectors. However, those centers of interest 'are disparate semantic categories: its ontogeny, their internal organization, nor its reach are the same' (Hernández Muñoz, 2006: 134). This article characterizes the centers of interest of the available lexicon tests and examines the taxonomies of the centers of interest proposed by different authors. Finally, it analyzes the organization of the lexical repertoires of Spanish as a Foreign Language, produced by a sample of 120 students from 3rd year in bilingual high school with Spanish in Warsaw (XXXIV Liceum), Kraków (VI Liceum) and Łódz (XXXII Liceum). Analysis gives attention to the type of partnerships that are prevalent in the bosom of the lexical sets, as well as describes in detail significant relationships that occur among the most frequent words.